2005
DOI: 10.1897/05-078r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect‐directed analysis of mutagens and ethoxyresorufin‐O‐deethylase inducers in aquatic sediments

Abstract: Sediment extracts from a creek in the Neckar river basin (Germany), which received the discharge of treated hospital wastewater, were found to exhibit strong aromatic hydrocarbon (Ah) receptor-mediated effects in a rainbow trout liver cell line (RTL-WI) as well as high mutagenicity in the Salmonella/microsome assay after fractionation. The crude extract did not exhibit a clear mutagenic response. Apparently, cleanup or fractionation before mutagenicity testing is necessary to minimize the risk of false-negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
84
1
10

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 45 publications
9
84
1
10
Order By: Relevance
“…For example, bioassays such as the rat hepatoma cell-line H4IIE test or EROD induction in RTL-W1 cells are widely used to assess the exposure to dioxin-like chemicals that bind to the aryl hydrocarbon receptor (AhR) (Brack et al 2005b(Brack et al , 2008aEngwall et al 1999;Hollert et al 2002;Kammann et al 2005b;Olsman et al 2007b). However, often the chemically detected dioxin-like equivalents (2,3,7,8-TCDD equivalents = TEQs) cannot explain the biological activity measured with the bioassay (bio-TEQ) (e.g., Brack et al 2005bBrack et al , 2008a.…”
Section: Current Eda Approaches and Their Limitationsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, bioassays such as the rat hepatoma cell-line H4IIE test or EROD induction in RTL-W1 cells are widely used to assess the exposure to dioxin-like chemicals that bind to the aryl hydrocarbon receptor (AhR) (Brack et al 2005b(Brack et al , 2008aEngwall et al 1999;Hollert et al 2002;Kammann et al 2005b;Olsman et al 2007b). However, often the chemically detected dioxin-like equivalents (2,3,7,8-TCDD equivalents = TEQs) cannot explain the biological activity measured with the bioassay (bio-TEQ) (e.g., Brack et al 2005bBrack et al , 2008a.…”
Section: Current Eda Approaches and Their Limitationsmentioning
confidence: 99%
“…For example, bioassays such as the rat hepatoma cell-line H4IIE test or EROD induction in RTL-W1 cells are widely used to assess the exposure to dioxin-like chemicals that bind to the aryl hydrocarbon receptor (AhR) (Brack et al 2005b(Brack et al , 2008aEngwall et al 1999;Hollert et al 2002;Kammann et al 2005b;Olsman et al 2007b). However, often the chemically detected dioxin-like equivalents (2,3,7,8-TCDD equivalents = TEQs) cannot explain the biological activity measured with the bioassay (bio-TEQ) (e.g., Brack et al 2005bBrack et al , 2008a. Similarly, attempts to correlate genotoxicity of complex environmental samples measured by tests such as the Ames, the micronucleus, or the comet assay with PAH concentrations often fail (Broman et al 1994;Gustavsson et al 2007;Kosmehl et al 2004;Reifferscheid et al 2008;Vahl et al 1997), suggesting a contribution of other nonregulated mutagens to the observed biological effect.…”
Section: Current Eda Approaches and Their Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have been conducted to characterize the endocrine potential of municipal effluents [24,25], surface water [26][27][28] and sediments [26,27,29,30], and there has been increasing awareness of the need for testing approaches targeting EDCs to be included into current environmental assessments and monitoring [31][32][33][34][35][36] …”
Section: Environmental Sources and Exposure To Edcsmentioning
confidence: 99%